STABILITY CONSTANTS FOR MONO- AND DIOXALATO-COMPLEXES OF Y AND THE REE, POTENTIALLY IMPORTANT SPECIES IN GROUNDWATERS AND SURFACE FRESHWATERS - Schijf J.; Byrne R.H. (My University, 2001)
We present the first measured set of stability constants for mono- and dioxalato-complexes of yttrium and all rare earths except Pm (Y+REE), Oxβn = [MOxn3-2n] [M3+]-1 [Ox2-]-n(where [ ] = concentrations, M = Y+REE, and Ox2- = C2O42-). Aqueous solutions of Y+REE were titrated with oxalic acid in the presence of a cation-exchange resin, and Y+REE concentrations in the solution phase were measured by ICP-MS. This method allows investigation of all Y+REE simultaneously under identical conditions and is thus very sensitive to subtle inter-element variations in log Oxβn. Experiments were performed at a single ionic strength (I = 0.05 M), but at two values of pH. Patterns of log Oxβ1 and log Oxβ2, determined from our experiments, are similar in shape and reminiscent of those for carbonato-complexes. The average ratio of stepwise stability constants K2/K1 = Oxβ2/(Oxβ1)2 is 0.05 +/- 0.02 for Y+REE excluding La and Ce.Literature values of Oxβ1(Eu) for 0.03 mol/L =< I =< 1 mol/L were used to derive the relation log Oxβ1(Eu) = log Oxβ10(Eu) - 6.132√I/(1 + 1.47√I) + 0.902I, where log Oxβ10(Eu) is the stability constant at infinite dilution. Applying this relation to all Y+REE, the following values of log Oxβ10 (at zero ionic strength) were found: 6.66 (Y), 5.87 (La), 5.97 (Ce), 6.25 (Pr), 6.31 (Nd), 6.43 (Sm), 6.52 (Eu), 6.53 (Gd), 6.63 (Tb), 6.74 (Dy), 6.77 (Ho), 6.83 (Er), 6.89 (Tm), 6.95 (Yb), 6.96 (Lu). These values, which are based on direct measurements for each individual Y+REE, agree quite well with published extrapolations that are mostly based on linear free-energy relationships.Total oxalate concentrations of 10-5-10-3 M have been reported for soil solutions. Free oxalate ions persist at much lower pH than free carbonate ions and a simple speciation model demonstrates that oxalato-complexes can dominate Y+REE speciation in mildly acidic groundwaters of low-to-moderate alkalinity.